(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article is dedicated to analyzing modern and innovative approaches to forming classroom communities in primary education from a scientific perspective. It comprehensively examines the psychological, pedagogical, and sociological foundations of community building, analyzing the effectiveness of methods such as collaborative learning, gamification, project-based learning, digital technologies, and the development of emotional intelligence. Based on scientific research and Uzbekistan’s educational practices, the article explores the impact of these methods on fostering students’ social skills, collaboration abilities, and sense of collective responsibility. It evaluates the influence of innovative approaches on the personal, social, and academic development of primary school students, while also addressing challenges faced in implementing these methods in Uzbekistan’s education system and proposing solutions to overcome them. Drawing on both Uzbek and international literature, practical recommendations are provided, serving as a guide for teachers and educators.